2D Necklace Flower Constellations applied to Earth observation missions. (January 2021) - Arnas, D.; Casanova, D.; Tresaco, E.
Abstract: This work focuses on the nominal design and later maintenance of satellite constellations based on the 2D Necklace Flower Constellations for their application in Earth observation missions. To that end, we introduce a generalization of the 2D Necklace Flower Constellations formulation to adapt the methodology to constellations whose satellites have different mission requirements, while still allowing to reduce the searching space in satellite constellation design. Moreover, this design is combined with its dual distribution in the Earth Centered–Earth Fixed reference frame to obtain additional information about the dynamic of the system, including the sub-satellite point revisiting time, or the relative to Earth distribution. This is used to optimize the constellation in terms of maximum uniformity of the distribution with respect to the Earth. Finally, a detailed example of application of this design methodology is presented, where a constellation based on satellites with different mission requirements is considered. Highlights: Generalization of 2D Necklace Flower Constellations for non uniform configurations. Methodology able to relate inertial and relative to Earth satellite distributions. Formulation of the problem in terms of Number Theory. Allows studying constellations whose satellites present different properties. Devised to reduce the searching space in optimization problems.